2020
DOI: 10.1177/1087054720928136
|View full text |Cite
|
Sign up to set email alerts
|

Which Child Will Benefit From a Behavioral Intervention for ADHD? A Pilot Study to Predict Intervention Efficacy From Individual Reward Sensitivity

Abstract: Objective: This article aims to assess whether individual differences in reward sensitivity can be used to predict which children with attention-deficit/hyperactivity disorder (ADHD) will benefit most from behavioral interventions that include reinforcement. Methods: A 12-week behavioral intervention was offered to 21 children with ADHD and their parents. Reward sensitivity was assessed prior to the intervention using a combination of psychological and physiological measures. ADHD symptoms were assessed pre- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 55 publications
0
0
1
Order By: Relevance
“…Although earlier attempts to identify child neurocognitive functioning as moderators on the effectiveness of behavioral parent training revealed mixed results (e.g., Adalio et al., 2018 ; van Langen et al., 2020 ), our results show the importance of neurocognitive functioning in the effectiveness of behavioral teacher training techniques. Our study differs from previous work in that we differentiated between the sets of techniques within behavioral training for ADHD, and found that, while all children benefited from antecedent‐based techniques, children with lower neurocognitive functions benefited more, or even only, from consequent‐based techniques.…”
Section: Discussioncontrasting
confidence: 51%
“…Although earlier attempts to identify child neurocognitive functioning as moderators on the effectiveness of behavioral parent training revealed mixed results (e.g., Adalio et al., 2018 ; van Langen et al., 2020 ), our results show the importance of neurocognitive functioning in the effectiveness of behavioral teacher training techniques. Our study differs from previous work in that we differentiated between the sets of techniques within behavioral training for ADHD, and found that, while all children benefited from antecedent‐based techniques, children with lower neurocognitive functions benefited more, or even only, from consequent‐based techniques.…”
Section: Discussioncontrasting
confidence: 51%